Кипренский - Бочаров Иван Николаевич (Жизнь замечат. людей: ЖЗЛ: Сер. биогр.: Осн. в 1933 г. М. Горьким, 1990)
Экземпляры: (20180815) / Инвентарный номер: 27084 / Цена: 3.00 / Сис.шифр: 85.143(2Р=Рус)5-8Кипренский / Авт.знак: Б86 /